Psychological flexibility as a mediator in the relationship between resilience and academic burnout among Doctor of Physical Therapy students: A structural equation modeling study - Jason Cherry; Gurpreet Singh; Michael Buck (Health Science Reports)
Abstract Background and Aims Although resilience has been identified as an important factor for mitigating burnout among health profession students, little is known regarding the modifiable factors that should be emphasized to improve resilience in this population. The purpose of this study was to evaluate psychological flexibility as a modifiable mediator of the relationship between resilience and academic burnout among healthcare students. Methods This cross‐sectional study was conducted with 369 Doctor of Physical Therapy (DPT) students from universities across the United States. A two‐stage structural equation modeling approach, including confirmatory factor analysis and structural path analysis, was used to investigate psychological flexibility as a mediator of the relationship between resilience and academic burnout. Results The measurement and structural path models demonstrated a good fit to the data. Resilience had a statistically significant indirect association with less academic burnout through psychological flexibility as the mediator (β = −0.32, 95% confidence interval = [−0.43, −0.08], p < 0.001). The direct relationship between resilience and academic burnout was not statistically significant (β = −0.19, p = 0.10). Conclusion These results indicate that the positive effects of resilience on academic burnout occur through modifiable psychological flexibility processes only. These results suggest that psychological flexibility is a modifiable mechanism through which resilience impacts academic burnout. Developing interventions focusing on psychological flexibility may help students build resilience and limit academic burnout, positively impacting the students, their future institutions, and their future patients.